What Are the Headwaters of Formal Savings? Experimental Evidence from Sri Lanka. (26th March 2019) - Callen, Michael; de Mel, Suresh; McIntosh, Craig; Woodruff, Christopher
Abstract: The world's poor are seeing a rapid expansion in access to formal savings accounts. What is the source of savings when households are connected to a formal account? We combine a high-frequency panel survey spanning two and a half years with an experiment in which a Sri Lankan bank used mobile Point-of-Service (POS) terminals to collect deposits directly from households each week. We find that the headwaters of formal savings lie in sacrificed leisure time: households work more, and improved savings options generate an increase in labour effort in both self-employment and in the wage market. The results suggest that the labour allocation channel is an important mechanism linking savings opportunities to income.